Critical Analysis of The Effectiveness of Pre-Hospital Emergency Care Models - Alshehri, Abdulaziz Mobshir; Alanazi, Saleh Barjas; Alenezi, Mansour Ali; Alanazi, Fawaz Fayez; Alanazi, Bader Farhan; Alanazi, Fahad Enad; Altayawi, Khalid Mohmmad; Alrashedi, Abdulrahman Saeed; Alrasheedi, Fahad Ali; Alanazi, Ali Saud (Journal of Ecohumanism, 2024)
A few years ago, prehospital emergency care was very important in the management of emergency conditions and in saving lives. Therefore, knowledge of the efficiency and effectiveness of the models in prehospital care is useful in predicting the future healthcare systems. The current paper provides this review of the successes and issues related to different models of prehospital emergency care based on the analysis of approaches used in various countries and the impact they have on various patients and their outcomes. The work contains the analysis of the literature review, comparison of models in HIM and LMICs, and the case-narrative synthesis of the systems to identify their strengths and weaknesses. Some learnings show that using advanced technologies, early admission, and the efficient coordination of the response system considerably improves patient outcomes. Nevertheless, prehospital emergency care practices require improvement in almost all sectors because of Resource limitations, including personnel, funding, and equipment; Inequality in the distribution of qualified personnel for emergency services; and inadequate training in handling cases.